Effective phage cocktail to combat the rising incidence of extensively drug-resistant Klebsiella pneumoniae sequence type 16. Issue 1 (31st December 2022) - Martins, Willames M. B. S.; Li, Mei; Sands, Kirsty; Lenzi, Michael H.; Portal, Edward; Mathias, Jordan; Dantas, Priscila P.; Migliavacca, Roberta; Hunter, James R.; Medeiros, Eduardo A.; Gales, Ana C.; Toleman, Mark A.
ABSTRACT: Bacteriophages are the most abundant organisms on Earth. As there are few effective treatment options against some pathogens, the interest in the bacteriophage control of multi-drug-resistant bacterial pathogens is escalating, especially for Klebsiella pneumoniae . This study aimed to develop a phage-based solution to the rising incidence of extensively drug-resistant clinical Klebsiella pneumoniae sequence type (ST16) infections starting from a set of phages recently characterized against this lineage. A phage-cocktail (Katrice-16) composed of eight lytic phages was characterized for potential use in humans. In vitro and in vivo broth inhibition and Galleria mellonella rescue assays were used to demonstrate the efficacy of this approach using a collection of 56 strains of K. pneumoniae ST16, with distinct genetic backgrounds that were collected from clinical infections from four disparate nations. Additionally, Katrice-16 anti-biofilm activity, synergism with meropenem, and activity in human body fluids were also assessed. Katrice-16 was highly active in vitro against our K. pneumoniae ST16 collection (AUC% median = 86.48%; Q1 = 83.8%; Q2 = 96.85%; Q3 = 98.85%). It additionally demonstrated excellent in vivo activity in G. mellonella rescue assays, even with larvae infected by isolates that exhibited moderate in vitro inhibition. We measured significant anti-biofilm activity over 12 h ( p = .0113) and synergic activity with meropenem. In addition, we also demonstrate that Katrice-16 maintained high activity in human body fluids. Our results indicate that our cocktail will likely be an effective solution for human infections with this increasingly prevalent and often highly resistant bacterial clone.